PERAN KEBIJAKAN DIVIDEN DALAM MEMODERASI PENGARUH PROFITABILITAS DAN LEVERAGE TERHADAP NILAI PERUSAHAAN - Regita Cahyani Febrianti; Sukandani, Yuni; Mipta, Miptaqul Rohma (Universitas PGRI Adi Buana, 2025)
Finding out how much of an impact Dividend Policy has on reducing or amplifying the effects of Profitability and Leverage on Company Value is the primary motivation for this study. Quantitative descriptive research is what this study is all about. The sample is comprised of 30 firms chosen using purposive selection methods. The entire population consists of 84 food and beverage subsector companies listed on the BEI for the 2021–2022 timeframe. Financial report documentation is used as a data collecting approach. Multiple linear regression analysis, the coefficient of determination test, Moderated Regression Analysis (MRA), the t-test, and the F-test are all part of the data analysis approach. It may be inferred that Dividend Policy moderates the simultaneous impact of Profitability and Leverage on Company Value, as the F test results show a significant value of 0.000 < 0.05. Meanwhile, the results of the t-test research show that Profitability influences Company Value with a significant value of 0.007 < 0.05, Leverage influences Company Value with a significant value of 0.000 < 0.05, Dividend Policy has a substantial impact on two variables: profitability and leverage. While dividend policy cannot mitigate the effect of profitability on company value (p = 0.145, > 0.05), it may limit the influence of leverage on company value (p = 0.026, < 0.05). Investors and would-be investors may use this research's findings as a basis for their decision-making process.